2014
DOI: 10.1007/s10984-014-9169-7
|View full text |Cite
|
Sign up to set email alerts
|

Learning English as a second language at the university level in Jordan: motivation, self-regulation and learning environment perceptions

Abstract: The overarching aim of this study was to investigate students' perceptions of the learning environment and whether these influenced their motivation and self-regulation in learning English as a second language at the university level in Jordan. Our sample involved 994 students, drawn from 13 schools, within three faculties (humanities, health sciences and engineering) of one university. The collection of data involved the administration of two surveys: one to assess students' perceptions of the learning enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 52 publications
6
27
1
2
Order By: Relevance
“…Our hypothesis, that there would be a direct relationship between four learning environment factors and three motivation factors, was generally supported. This finding corroborates those of past studies carried out in Western settings (see for example, Chipangura and Aldridge 2017; Tas 2016) as well as a study carried out at the university level in Jordan (Alzubaidi et al 2016), which also found relationships between the learning environment and student motivation. A significant contribution of this study, therefore, is that it identifies malleable factors within the learning environment that positively influence the motivation of female students in science classes.…”
Section: Influence Of the Learning Environment On Student Motivation (Hypothesis 1)supporting
confidence: 91%
See 1 more Smart Citation
“…Our hypothesis, that there would be a direct relationship between four learning environment factors and three motivation factors, was generally supported. This finding corroborates those of past studies carried out in Western settings (see for example, Chipangura and Aldridge 2017; Tas 2016) as well as a study carried out at the university level in Jordan (Alzubaidi et al 2016), which also found relationships between the learning environment and student motivation. A significant contribution of this study, therefore, is that it identifies malleable factors within the learning environment that positively influence the motivation of female students in science classes.…”
Section: Influence Of the Learning Environment On Student Motivation (Hypothesis 1)supporting
confidence: 91%
“…The findings have implications for teachers in terms of the role that they play in shaping the learning environment including the approaches to learning and the learning structures that they provide. Second, the positive influence of teacher support on task value also supports the findings of past research carried out in Western countries (see for example, Bell & Aldridge 2014; and in Jordan (Alzubaidi et al 2016). Given that task value beliefs promote learning performance (Zhang, Hawk, Zhang and Zhao 2016) and influence the effort students apply to a range of tasks (Andrade andHeritage 2017, Nagengast et al 2011), this finding draws attention to the important role that teachers have in helping students to value learning tasks.…”
Section: Teacher Supportsupporting
confidence: 78%
“…In the discussion of the effects of glocal learning contexts on the second language learner motivation, the learning setting can be observed to influence the motivational levels of the learners in two ways. The first factor pertains to the perceptions of learners regarding the learning environment, which was underlined as a powerful factor by Alzubaidi, Aldridge, and Khine (2016). As also proposed by Ushioda (2009), learners go through processes of meaning-making, and they construe their learning experiences in the light of their perceptions stemming from their experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Salah satunya adalah motivasi. Motivasi memiliki peranan yang penting dalam pengembangan kemampuan berbicara siswa (Alzubaidi, Aldridge & Khine, 2016). Dalam hal ini peneliti akan mengangkat masalah peningkatan motivasi mahasiswa dalam berbicara dalam bahasa Inggris dengan menggunakan Crazy Story Game.…”
Section: Pendahuluanunclassified